Mechanical Properties of Composites Combination of Areca Fronds with Epoxy Resin - Joni Joni; Enos Tambing (University of Merdeka Malang, 2023)
Technological advances in material aspects are always increasing, and one of the applications of natural fibers as a matrix in composite materials has begun to be widely used. Composite materials have mechanical properties that are sturdy, corrosion resistant, and concise, and can be used as a substitute for metal materials. Areca palm fronds are part of the areca palm tree which are widely used as storage media because they are durable and weather resistant. The aim of this study was to determine the tensile strength of areca nut composites without alkali treatment combined with epoxy. Tensile test based on ASTM D3039 test standard. The test results showed a maximum tensile strength of 4839886.67 N/m2 or 4.84 MPa, and a modulus of elasticity of 114148270.5 N/m2 or 114.15 MPa. According to the JIS A 5905 standard, it meets the specified requirements, namely elastic strength of 32 MPa and tensile strength of 0.4 MPa.